Le renouveau de la « French connection » avec l’Afrique du Sud (1995-2015) - Brigitte Senut (Revue de Primatologie)
French palaeontological research in South Africa has been revived after a protocol of collaboration was signed between institutions. Several fruitful projects were initiated especially in Miocene and Plio-Pleistocene palaeontology as evidenced by the results obtained in Namaqualand—discoveries of a Lower Miocene fauna at Bosluis Pan, of the first hominoid from subequatorial Africa and of Upper Miocene deposits in the Areb Hills—but also in the Cradle of Humankind. These new dynamic researches are important for the future of the palaeoprimatology (including human palaeontology), as they indicate that the scenarios concerning our origins which are generally centered on East Africa must be revised. The South Africa sub-region has a strong palaeontological potential to fuel the debates.